On The use of modified data envelopment analysis models for product line selection - Semiromi, Mohammad Elashem Davoodi (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2014)
ABSTRACT: The process of converting the raw materials to a final product in a factory is called production line. These processes include refinement, purification and assembly. Afterward, selection of best production line would be the next step which leads to determining the best product. Now to make the choice easier this thesis proposes a method based on Data Envelopment Analysis (DEA) for product line selection. DEA is a technique based on simple linear programming. This method is often used to measure the performance of Decision Making Units (DMUs) and to choose the most efficient ones which could generate multiple outputs via multiple inputs. DEA has been used in different sciences from mechanical and industrial engineering to economics and finance and results show that the accuracy of method is substantial. The method has not been applied to product line selection problem before, though. Hence this study tries to investigate the matter on product line selection problem by testing the DEA methodology. To generate the evidence in a quantitative manner, a real life sample is discussed and the results are argued. The results of this study are expected to be used by managers to make the correct decisions in order to achieve both maximum consumers' satisfaction and maximum profitability. Keyword: Product Line Selection, Data Envelopment Analysis, Linear Programing. ………………………………………………………………………………………………………………………………………………………………………………………………………… ÖZ: Bir fabrikada ham maddelerin nihai ürüne dönüştürülme işlemine üretim hattı denir. Bu işlemler arıtma, tesfiye ve sentez aşamalarıni içerir. Bir sonraki aşamada, en uygun ürün hattı seçimi için, en iyi ürünün belirlenmesi gerekir. Bunun belirlenmesini kolaylaştırmayı amaçlayarak, bu tez Veri Zarflama Analizi (Data Envelopment Analysis) yöntemini ürün hattı seçimi için önermektedir. Veri Zarflama Analizi (DEA) basit bir çizgisel programlama tekniğidir. Bu yöntem genellikle karar verme birimlerinin (DMUs) performansını ölçmek ve çoklu girişleri ve çıkışları göz önünde bulundurarak en verimli ürünü seçmek için kullanılır. DEA mekanik ve endüstriyel mühendislik, ekonomi ve finans gibi farklı bilim dallarında da kullanılıyor ve elde edilen sonuçlar yöntemin doğruluğunu kanıtlamaktadır. Bu çalışma daha önce ürün hattı seçim problemi üzerine uygulanmadığı için, DEA metodolojisi yardımı ile incelenir. Bu tezde gerçek bir ürün kullanılmakta ve sonuçlar tartışılmaktadır. Araştırma sonuçlarının maksimum tüketici memnuniyeti ve maksimum kar elde edilmesi amaçlanarak yöneticiler tarafından kullanılması beklenmektedir. Anahtar Kelime: Ürün hattı seçimi, Veri zarflama analizi, Çizgisel programlama.
Master of Science in Mechanical Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Mechanical Engineering, 2014. Supervisor: Prof. Dr. Majid Hashemipour.
Keywords: Mechanical Engineering; Production management; Product Line Selection, Data Envelopment Analysis, Linear Programing